De quelle éducation au politique l’évaluation PISA de la « compétence globale » est-elle porteuse ? - Jean-Émile Charlier; Sarah Croché (Éducation et Socialisation)
Sustainable Development Goals (SDGs), adopted by the 193 Member States of the United Nations in September 2015, are presented as "17 Goals to Transform our World" (Sustainable development (un.org)). These prospects provide answers to the main challenges facing humanity, including those linked to “poverty, inequality, climate change, environmental degradation, prosperity, peace and justice” (id.) to all countries. The related goals carry on a political education program that can be considered transversally in every target envisaged, mainly in educational terms. This paper focuses on those related to education for sustainable development, and more precisely to the evaluation organized by the PISA program of the OECD by measuring "global competence”.